The Effect of Leverage and Company Size on Profitability at PT. Mayora Indah - Putriana Dewi, Nazwa; Hernawati, Euis (International Research & Development for Human Beings (IRDH), 2025)
This research aims to examine the influence of leverage and firm size on the profitability of PT. Mayora Indah Tbk. The study utilized a quantitative methodology, incorporating multiple linear regression analysis as a key component of its framework. We measured the leverage variable using the Debt-to-Equity Ratio (DER) and evaluated the firm size variable using the natural logarithm of total assets (Ln total assets). This research was conducted at PT. Mayora Indah Tbk, employing the annual financial statements accessible on the IDX for the timeframe of 2020-2024. The findings of this study demonstrate that leverage exerts a positive and significant impact on profitability. This work suggests that a rise in leverage is associated with an increase in profitability, while a reduction in leverage corresponds to a decline in profitability; meanwhile, firm size appears to have no impact on profitability. This evidence suggests that the size of the company will not affect its profitability. The analysis examines how indebtedness and organizational scale concurrently impact the financial performance of PT. Mayora Indah Tbk. The leadership at PT. Mayora Indah Tbk should focus on the management of leverage to maintain and improve the company's profitability, as simple expansion does not ensure enhanced profitability without adequate efficiency and a well-conceived business strategy.